Penerapan Metode Design Thinking Kembel Dalam Pengembangan Mebel Modular Pada Lounge Rekarasa Universitas Kristen Petra - Ryan Sidharta Pribadi Santoso; Mariana Wibowo; Filipus Priyo Suprobo (Intra, 2019)
The Rekarasa lounge in Petra Christian University is a facility that is used to stop by and lay back, which will be a study center. In the execution process, the lounge visitors are dominated by the students of Hospitality Management Department, and visitors which have a specific need (For example meetings and to greet guests). In the development plan that is carried out in the Rekarasa lounge, the author takes this opportunity to do researches to develop facilities for the lounge in order for it to be an excellent study center, by using facilities to attract students in Petra Christian University. By using Kembel’s design thinking, the development can be efficient and right on target, through processes which are defining the problem, data grouping, sistematical analysis, making a prototype and testing to accommodate the different needs of the user. After the testing phase, the final phase is the implementation phase which evaluates whether the product is sustainable or not and evaluating the effects and impacts that was made by the product solution. With the space limitations, the solution for it is a flexible and modular based facility. The design output are tables, chairs, stools, puffs and a side table. Therefore, it can be made into a business model as well as brand to be marketed to fulfill the various needs of the society also.